2020
DOI: 10.1021/jacs.0c03786
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Mechanism for Thiol-Induced Photoswitching and Photostability of Cyanine Dyes

Abstract: Cyanines (Cy3, Cy5, Cy3B) are the most utilized dyes for single-molecule fluorescence and localization-based super-resolution imaging. These modalities exploit cyanines’ versatile photochemical behavior with thiols. A mechanism reconciling seemingly divergent results and enabling control over cyanine photoreactivity is however missing. Utilizing single-molecule fluorescence on Cy5 and Cy5B, transient-absorption spectroscopy, and DFT modeling on a range of cyanine dyes, herein we show that photoinduced electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 50 publications
3
96
0
3
Order By: Relevance
“…The reference Cy‐C without a secondary amine group further demonstrated that the amino group as electron donor plays the key role for the PeT process. This proposed radical‐mediated photolysis is consistent with the reported cyanines [10f] . Finally, with the help of water as a reactant, the photolysis fragments H‐Cy are obtained.…”
Section: Introductionsupporting
confidence: 89%
“…The reference Cy‐C without a secondary amine group further demonstrated that the amino group as electron donor plays the key role for the PeT process. This proposed radical‐mediated photolysis is consistent with the reported cyanines [10f] . Finally, with the help of water as a reactant, the photolysis fragments H‐Cy are obtained.…”
Section: Introductionsupporting
confidence: 89%
“…dyes routinely used for superresolution STORM. By contrast, our fDAEs do not require strict chemical control of the imaging conditions (48,49). The Urbach tail absorption of the OFs allowed us to apply just a 532-or 561-nm laser in order to induce single-molecule photoswitching (blinking) and acquire superresolution images.…”
Section: Chemistrymentioning
confidence: 99%
“…We previously reported that these conformationally restricted cyanines do not undergo efficient blinking under conventional high‐thiol d STORM conditions. Instead, these probes exhibit improved recovery from NaBH 4 reduction, providing high‐quality SMLM imaging when appended to a small molecule targeting agent [3a, 27] …”
Section: Resultsmentioning
confidence: 99%